(untitled) - Lednicky, Martin; Sosedova, Jarmila (Doprava a spoje, 2010)
In the upper part of the Danube there are five austria ports of international importance between the port of Vienna to the port of the Linz. The ports are part of logistics chains in which cargo is transported from sender to customer by various means of transport. Ports differ in their equipment and cargo is transfered and storaged in the ports which have got specific transhipment and storage facilities